Financial structure and relative importance of financial institutions - a Malaysian case - Ismail Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 1982)
This study investigates the relative importance of financial institutions in the process of financial and economic development in Malaysia between 1960 - 1974. The analysis begins with the determination of the size and character of financial superstructure and the relative importance of various types offinancial instruments, compared with the real infrastructure of national product. Using Goldsmith's FIR (Financial III terrelation Ratio) model it was found that Malaysia had experienced a period of positive changes in the growth of financial development.